The Effect Of The Guided Inquiry Learning Model On Spatial Thinking Skills Viewed From Students Geoliteracy - Candra Adityatama; Budi Handoyo; Heni Masruroh (STKIP Singkawang, 2025)
The guided inquiry (GI) model is one of the scientific learning models that is student centered and designed to stimulate spatial thinking skills through discovery activities under the guidance and direction of the teacher. In addition to the learning model, geoliteracy is another factor that influences students spatial thinking skills. This study aims to determine the effect of the GI model on spatial thinking skills and to examine the effect of the GI learning model on spatial thinking skills in terms of students geoliteracy. The research method is a quasi experimental design with a post test only design. The population of this study consists of eleventh grade students at SMAN 5 Malang and SMAN 6 Malang, with purposive sampling used to determine the control and experimental classes at each school. Data were collected using a test instrument to obtain spatial thinking ability scores and geoliteracy scores. Data analysis was carried out using independent sample t tests and two way anova. The results show that the GI model can affect the spatial thinking skills possessed by students, even though both experimental classes received the GI model treatment. Further results indicate that the GI model can affect spatial thinking skills in terms of students geoliteracy. However, there is a significant difference in spatial thinking skills based on geoliteracy between students at SMAN 6 Malang and students at SMAN 5 Malang, even though both experimental classes received the GI model treatment.